2022
DOI: 10.3390/ijns8040056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Laboratory Protocol for Newborn Screening for Congenital Adrenal Hyperplasia in New Zealand

Abstract: Between 2005 and 2021, 49 cases of classical congenital adrenal hyperplasia were diagnosed in New Zealand, 39 were detected in newborns and 10 were not detected by screening. For every case of CAH detected by screening, 10 false-positive tests are encountered. Second-tier liquid chromatography-tandem mass spectrometry (LCMSMS) has the potential to improve screening sensitivity and specificity. A new laboratory protocol for newborn screening for CAH was evaluated. Birthweight-adjusted thresholds for first- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Screening for CAH has been implemented in neonatal screening programs in several countries worldwide, with the aim to achieve early identification of newborns with SW CAH to prevent salt-wasting adrenal crisis and reduce mortality. 3 , 18 Since the screening has a very high sensitivity for SW CAH, 7 , 9 prevalence estimates of SW CAH among newborns participating in screening are available from several countries. 3 In screening studies from countries with health care systems comparable to the Danish system, the reported prevalence of SW CAH range from 3.4 to 5.5 per 100,000 newborns (Sweden: 148 cases among ∼2,700,000 newborns 11 ; Netherlands: 114 cases among 2,235,931 newborns 19 ; New Zealand: 40 cases among 1,175,973 newborns 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening for CAH has been implemented in neonatal screening programs in several countries worldwide, with the aim to achieve early identification of newborns with SW CAH to prevent salt-wasting adrenal crisis and reduce mortality. 3 , 18 Since the screening has a very high sensitivity for SW CAH, 7 , 9 prevalence estimates of SW CAH among newborns participating in screening are available from several countries. 3 In screening studies from countries with health care systems comparable to the Danish system, the reported prevalence of SW CAH range from 3.4 to 5.5 per 100,000 newborns (Sweden: 148 cases among ∼2,700,000 newborns 11 ; Netherlands: 114 cases among 2,235,931 newborns 19 ; New Zealand: 40 cases among 1,175,973 newborns 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…17-OHP is the preferred metabolite for screening and reflects the residual activity of 21-hydroxylase. 21 Depending on the cut-off level, screening detects some newborns with SV CAH, and seldom also NC CAH, 7 , 9 , 10 though NC CAH is not a target disease of the screening. In the screening study from the Netherlands, 19 14 newborns with SV CAH were detected at screening, corresponding to a prevalence of 0.6 per 100,000.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective analysis of 143 cases of CAH identified by newborn screening over 26 years in Sweden, the sensitivity of screening for SW-CAH, SV-CAH and NC-CAH were 100%, 79.7% and 32.4% respectively when molecular analysis was used to define disease classification ( 13 ). Higher 17OHP thresholds for babies born before term will improve the PPV of screening but may reduce the screening sensitivity for SV-CAH, although cases will be missed even with low screening thresholds for 17OHP ( 14 , 15 ). In general, variations in screening accuracy can also be associated with differences in the timing of sample collection ( 16 ), the number of repeat samples collected ( 9 , 16 ), whether second tier testing is used as part of the screening pathway ( 17 ) and how different screening programmes define a positive screening test.…”
Section: Newborn Screening For Cahmentioning
confidence: 99%
“…However, collection of additional later samples, such as occurs routinely in two-screen states, increases the sensitivity of screening for SV-CAH and NC-CAH ( 9 ). In recent years, many screening protocols have incorporated second-tier liquid chromatography-tandem mass spectrometry testing, which accurately measures multiple informative steroids simultaneously and can further improve the efficiency of screening ( 15 , 18 , 19 ).…”
Section: Newborn Screening For Cahmentioning
confidence: 99%